Calibration Free Laser Induced Breakdown Spectroscopy (CF-LIBS) as a tool for Quantitative Elemental Analysis of Iraqi Cement - Hamad, Tagreed K; Ali, Alaa H; Salloom, Hussein T; Ghazai, Alaa J (Al-Nahrain Journal of Science, 2018)
Laser-induced breakdown spectroscopy (LIBS) is a promising atomic emission based elemental analysis technique that has many potential applications for various samples. This paper presents the implementation of calibration free laser induced breakdown spectroscopy (CF-LIBS) approach to identify and determine the concentration of elements in Iraqi cement samples collected from local market. Q-switched Nd: YAG laser with energy laser pulse of 100 mJ and pulse duration of 9 ns is focused on cement pellet surface to generate a plasma spark in air. The plasma emission spectrum was recorded by the spectrometer connected to the fiber optic and resolved spectra were used for identification and quantification of detected elements. The produced plasma temperature was obtained from the Boltzmann plot method while their electron density was determined by Saha-Boltzmann equation. The major elements such as Ca, Si, Al, Fe, Mg and minor Mn, Ti, K and Na elements have been identified and their concentrations calculated based on analysis of the spectrum that contain all information  needed to derive the elemental composition of the  cement matrix.